Improving Junior High School Students’ Reading Comprehension of Recount Texts through Mind Mapping - Rosa Dalima Naben; Thresia Trivict Semiun; Delti Yulita; Erlinda Sonya Pale (International Journal of English Education and Linguistics (IJoEEL), 2026)
Reading is one of the four essential language skills in language learning. Its role is not only to support language competence but also to broaden knowledge. However, students’ reading comprehension ability remains unsatisfactory. This research aims to improve the reading comprehension of seventh-grade students at SMPN I Miomaffo Timur through the use of mind mapping technique. Specifically, it investigates: (1) the extent to which mind mapping improves students’ reading comprehension, and (2) the common mistakes made by students in comprehending texts. A pre-experimental design with pre-test and post-test was employed. The pre-test results showed that 60% of students performed very poorly, 30% poorly, 10% fairly, and none performed well. In contrast, the post-test indicated significant progress, with 15% of students achieving very good scores, 75% good, and 10% fair. These findings demonstrate that mind mapping is effective in enhancing students’ reading comprehension, particularly in understanding recount texts. The common difficulties identified in the pre-test were related to stated detail questions, identifying the main idea, determining the purpose of the text, and recognizing text type. In the post-test, the remaining challenges were mainly in identifying the main idea, understanding details, and determining the purpose of the text. Overall, the study concludes that mind mapping positively impacts students’ reading comprehension and helps minimize common reading difficulties.